1999
DOI: 10.1148/radiology.212.1.r99jl04133
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous Pathway for Acupuncture Stimulation: Localization of Processing with Functional MR Imaging of the Brain—Preliminary Experience

Abstract: Functional MR imaging can demonstrate the CNS pathway for acupuncture stimulation. Acupuncture at ST.36 and LI.4 activates structures of descending antinociceptive pathway and deactivates multiple limbic areas subserving pain association. These findings may shed light on the CNS mechanism of acupuncture analgesia and form a basis for future investigations of endogenous pain modulation circuits in the human brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
246
2
10

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 395 publications
(278 citation statements)
references
References 35 publications
20
246
2
10
Order By: Relevance
“…Recently, functional magnetic resonance imaging (fMRI) has been used to investigate the neurobiological mechanisms underlying acupuncture needle manipulation [11,20,22,24,25,29,[42][43][44][45]. It is commonly reported that manual acupuncture needle manipulation induces fMRI signal change in widespread neuronal networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, functional magnetic resonance imaging (fMRI) has been used to investigate the neurobiological mechanisms underlying acupuncture needle manipulation [11,20,22,24,25,29,[42][43][44][45]. It is commonly reported that manual acupuncture needle manipulation induces fMRI signal change in widespread neuronal networks.…”
Section: Discussionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) and Positron Emission Tomography (PET) studies of acupuncture needle manipulation [3,11,[20][21][22]24,25,29,31,[42][43][44] and acupuncture analgesia [5,45,46] demonstrate involvement of these neuronal networks during acupuncture. Additionally, there is strong evidence that acupuncture analgesia is mediated at least in part by opioid systems [4,6,26,32].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [31] demonstrated that electroacupuncture stimulation (EAS) at two pairs of acupoints in the same spinal segment evokes specific responses in brain images obtained with fMRI. The studies of Hui et al and Wu et al [20,28,29] on acupoint ST 36 showed significant modulatory effects on the limbic system, paralimbic and subcortical gray structures, while control stimulation showed strong activation mainly at the somatosensory cortex. Kong et al [21] studied activa-tion patterns evoked by manual and electroacupuncture, showing that electroacupuncture mainly produced fMRI signal increases in the precentral and postcentral gyri, inferior parietal lobule (IPL), and putamen/insula.…”
Section: Introductionmentioning
confidence: 89%
“…These previous acupuncture studies [7,31,20,28,29,21,30] were mainly based on multiple-block design, and fMRI data were analyzed using the whole block paradigm. However, from our analysis, we found that the 'on-state,' during which needle manipulation was performed, consisted of three main components: mechanical stimulation due to needle manipulation, subject expectation of what they would experience and the actual acupuncture effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation